# Simplify the expression : 7(9k + 8) + 3 ( k-10)

### 5 Answers | Add Yours

Let E =7(9k+8) + 3(k-10)

First we will expand the brackets:

we will distribute 7:

==> E = 7*9k + 7*8 + 3*k + 3*-10

= 63k + 56 + 3k - 30

Now will group similar terms:

==> E = 63k + 3k + 56 - 30

= 66k + 26

**Then E = 66k + 26 **

To simplify 7(9k + 8) + 3 ( k-10) we first open the brackets.

Therefore 7(9k + 8) + 3 ( k-10)

= 7*9k + 7*8 + 3*k – 3*10

= 63k + 56 + 3k -30

add the common terms

=> 63k + 3k + 56 – 30

=> 66k + 26

**Therefore 7(9k + 8) + 3 ( k-10) is equal to 66k + 26**

7(9k + 8) + 3 ( k-10) first multiply the contents of the parenthesis with the outside number

63k+56+3k-30 add the k's

66k+56-30 subtract 30 from 56

66k+26 is your answer

7 ( 9k + 8 ) + 3 ( k - 10 )

First distribute

By distributing your equation should look like

**63k + 56 + 3k - 30 **now combine all the like terms ( 63k with 3k and 56 with -30 )

By combining, your equation should look like

**66k + 26 **which is your answer

7(9k + 8) + 3 ( k-10)

multiply the number inside the parentheses by the numbers outside.

`7 xx 9k= 63k `

`7 xx 8 = 56 `

`3 xx k = 3k `

`3 xx -10= -30 `

combine like terms

`63k + 3k + 56 - 30 `

**66k - 26 **